(untitled) (International relations and international law Journal, 2023)
The European Union (EU) is one of the key partners for the Republic of Kazakhstan. In 2015, the European Union and the Republic of Kazakhstan signed the Enhanced Partnership and Cooperation Agreement (EPCA), which replaced the previous Partnership and Cooperation Agreement (PCA). This article aims to explore the evolution of partnership priorities by analyzing these two documents, the PCA and EPCA. The main objective of this article is to evaluate the general fields of cooperation between the European Union and Kazakhstan as outlined in both agreements, and how they have changed over some time. This will be done using a quantitative content analysis with manual word frequency counting. The theoretical foundation of the paper includes examining the role of the PCA and EPCA in European Union’s foreign policy, conducting a literature review on European Union -Kazakhstan relations, and providing background information on the political, economic, environmental, and other ties between the European Union and the Republic of Kazakhstan. Consequently, this article summarizes the priorities of the European-Kazakh relationship and their evolution over time, employing an empirical approach through the text analysis of the two agreements. Key words: European Union, Kazakhstan, PCA, EPCA, content analysis.